Analysis of the Single Index Model and Markowitz in Optimal Portfolio Selection in the Telecommunications Sub-Sector Listed on the Indonesia Stock Exchange for the Period 2020-2022 - Devira Larasati; Ari Rohmana; Reza Mutiara; Maria Yovita R. Pandin (Finance : International Journal of Management Finance, 2023)
This study, which uses qualitative methodology, compares and finds the best results from two approaches, namely the Markowitz model and the single index model to build an optimal portfolio. The population of this study consists of all stocks included in the telecommunications subsector listed on the Indonesia Stock Exchange for the period 2020-2022. Purposive sampling is used in this study to select samples. There are 5 candidate company stocks that meet the requirements in the sample criteria. From the results of the research conducted, it proves that with the single index model method, 3 stocks are included in the optimal portfolio, namely PT Tower Bersama Infrastructure Tbk (TBIG) with a proportion of 50%, PT Visi Telekomunikasi Infrastruktur Tbk (GOLD) with a proportion of 15%, and PT Indosat Ooredoo Hutchison Tbk (ISAT) with a proportion of 35%. From the research results of these 3 stocks to form an optimal portfolio, the expected return is 2% and the risk borne is 18%. While for the Markowitz model, 3 stocks were obtained as optimal portfolio candidates, namely PT Telekomunikasi Indonesia Tbk (TLKM) with a proportion of 68%, PT Visi Telekomunikasi Infrastruktur Tbk (GOLD) with a proportion of 15%, and PT Tower Bersama Infrastructure Tbk (TBIG) with a proportion of 17%. From the research results of these 3 stocks to form the optimal portfolio, the expected return is 1% and the risk borne is 6%.